Opportunities and Challenges of the Shariah Film Industry in the Global Market - Nurintan Siregar; Saifuddin Yuliar; Adam Malik Indra; Herlinda Herlinda (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The sharia film industry is part from economy creative based values that have potential big for growing in the global market along with increasing request to content entertainment that prioritizes ethics, humanit, and spirituality. Research aim for analyze opportunities and challenges sharia film industry in global market dynamics and the implications to development economy global creative research this use approach qualitative descriptive with method studies bibliography. Data obtained from book scientific, articles journals and publications related film industry, economy creative, as well as film- based sharia values, which are analyzed use technique analysis content. Research results show that the sharia film industry has significant opportunity through digital platform support, growth the world's Muslim population, and the increasing interest towards value-based content. However thus, the industry This Still face challenge structural and cultural, such as limitations capital, sources Power humans, regulations, and global market perception tends to view sharia films as exclusive products. Research This conclude that development The sharia film industry requires an adaptive strategy that integrates sharia values with universal narrative, reinforcement ecosystem industry, as well as support sustainable policies to be able to empowered compete and contribute optimally in economy global creative. The Implications of this study suggest that policy makers must develop standardized Halal governance for the creative sector, while producers must move toward Values-based Storytelling to reach broader, non-Muslim audiences seeking ethical alternatives. Ultimately, this research provides a comprehensive roadmap for the Shariah film industry to evolve into a competitive, ethically-driven force within the global creative economy.